Between Fidelity and Reform: Muḥammad Qāsim Nanotvi's (1833–1880) Rearticulation of Waḥdat al-Wujūd - Safaruk Chowdhury (Teosofia: Indonesian Journal of Islamic Mysticism, 2025)
Muhammad Qasim Nanotvi (1833–1880) is primarily recognized as the founder of the Deoband seminary. His engagement with waḥdat al-wujūd reveals a neglected philosophical project that seeks to reconcile mystical intuition with rigorous metaphysical reasoning. Drawing on the intellectual legacy of Shāh Walīullāh al-Dihlawī and Ḥājī Imdādullāh Muhājir Makkī, Nanotvi affirms that all existence depends on God, yet rearticulates this within a theological structure that safeguards divine transcendence. This article examines Nanotvi's reinterpretation of waḥdat al-wujūd (the unity of being), a foundational yet contested concept in Islamic metaphysics and Sufi thought. Employing a historical-critical approach, this study reveals that Nanotvi does not fully endorse waḥdat al-wujūd but rearticulates it as the unity of the attribute of existence (ṣifāt al-wujūd), emphasizing that all existence depends on God while preserving divine transcendence and ontological distinctions between God and creation. By focusing on the attribute of existence, Nanotvi offers a systematic response to ontological debates, avoiding the controversies surrounding waḥdat al-wujūd, while maintaining the spiritual depth of this concept. Contribution: The findings contribute to a deeper understanding of how Islamic thinkers navigate complex metaphysical questions, offering valuable insights for addressing the tensions between mysticism and orthodoxy.